Adenoidectomy versus chemoprophylaxis and placebo for recurrent acute otitis media in children aged under 2 years: randomised controlled trial. Issue 7438 (9th February 2004) - Koivunen, Petri; Uhari, Matti; Luotonen, Jukka; Kristo, Aila; Raski, Risto; Pokka, Tytti; Alho, Olli-Pekka
Abstract: Objective To evaluate the efficacy of adenoidectomy compared with long term chemoprophylaxis and placebo in the prevention of recurrent acute otitis media in children aged between 10 months and 2 years. Design Randomised, double blind, controlled trial. Setting Oulu University Hospital, a tertiary centre in Finland. Participants 180 children aged 10 months to 2 years with recurrent acute otitis media. Intervention Adenoidectomy, sulfafurazole (sulphisoxazole) 50 mg/kg body weight, given once a day for six months or placebo. Follow up lasted for two years, during which time all symptoms and episodes of acute otitis media were recorded. Main outcome measures Intervention failure (two episodes in two months or three in six months or persistent effusion) during follow up, number of episodes of acute otitis media, number of visits to a doctor because of any infection, and antibiotic prescriptions Number of prescriptions, and days with symptoms of respiratory infection. Results Compared with placebo, interventions failed during both the first six months and the rest of the follow up period of 24 months similarly in the adenoidectomy and chemoprophylaxis groups (at six months the differences in risk were 10% (95% confidence interval −9% to 29%) and 18% (−2% to 38%), respectively). No significant differences were observed between the groups in the numbers of episodes of acute otitis media, visits to a doctor, antibiotic prescriptions, and days with symptoms of respiratory infection. Conclusions Adenoidectomy, as the first surgical treatment of children aged 10 to 24 months with recurrent acute otitis media, is not effective in preventing further episodes. It cannot be recommended as the primary method of prophylaxis.